Analisis Pengendalian Persediaan Bahan Baku Tepung Terigu dengan Metode Material Requirement Planning pada Boy’s Cake And Bakery di Sukoharjo - Akbar Febrianto; Sunarso (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The research  to compare the costs of controlling raw material inventory between the policies implemented by Boy's Cake and Bakery in Sukohajo using the MRP method. The MRP method is expected to reduce the risk of running out of stock so that it does not disrupt the production process of Boy's Cake and Bakery in Sukohajo, as well as increasing the efficiency of raw material supplies. The aim of these two methods is to consider the right ordering time and determine the optimal amount of raw material inventory. At the analysis stage, an evaluation was carried out on the application of the Material Requirement Planning (MRP) method to increase efficiency in planning raw material supplies at Boy's cake and Bakery in Sukoharjo.The results of this research show that the cost of raw material inventory using the Lot For Lot (LFL) method is Rp. 204,000, the Economic Order Quantity (EOQ) method is Rp. 548,500, and the Period Order Quantity (POQ) method is Rp. 204,000. Meanwhile, the total cost of raw material supplies according to the management policy of Boy's Cake and Bakery in Sukoharjo is Rp. 1,132,000. The application of the Material Requirement Planning (MRP) method at Boy's cake and Bakery in Sukoharjo can increase the efficiency of raw material inventory planning, with the Lot For Lot (LFL) and Period Order Quantity (POQ) technique proven to be the most effective. From these results, it can be seen that the raw material inventory costs according to the policy of the owner of Boy's Cake and Bakery in Sukoharjo are greater than the raw material inventory costs using the MRP method.